2001
DOI: 10.1074/jbc.m010725200
|View full text |Cite
|
Sign up to set email alerts
|

Serine Proteinase Inhibitor 3 and Murinoglobulin I Are Potent Inhibitors of Neuropsin in Adult Mouse Brain

Abstract: Extracellular serine protease neuropsin (NP) is expressed in the forebrain limbic area of adult brain and is implicated in synaptic plasticity. We screened for endogenous NP inhibitors with recombinant NP (r-NP) from extracts of the hippocampus and the cerebral cortex in adult mouse brain. Two SDS-stable complexes were detected, and after their purification, peptide sequences were determined by amino acid sequencing and mass spectrometry, revealing that target molecules were serine proteinase inhibitor-3 (SPI3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
37
0
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 68 publications
1
37
0
1
Order By: Relevance
“…Similar results have been found in brain injury detected by microarray (98) and in segmental nerve ligation injury detected by proteomics analysis (99). Interestingly it was found that CPI3 belongs to the subfamily of serpins (100), and its proposed function is to inactivate neuropsin and to control the level of neuropsin in adult mouse brain (101). Up-regulation of CPI3 in SCI rat might indicate the necessity of the damaged tissue to counteract the excess amount of proteases induced after SCI.…”
Section: Discussionsupporting
confidence: 71%
“…Similar results have been found in brain injury detected by microarray (98) and in segmental nerve ligation injury detected by proteomics analysis (99). Interestingly it was found that CPI3 belongs to the subfamily of serpins (100), and its proposed function is to inactivate neuropsin and to control the level of neuropsin in adult mouse brain (101). Up-regulation of CPI3 in SCI rat might indicate the necessity of the damaged tissue to counteract the excess amount of proteases induced after SCI.…”
Section: Discussionsupporting
confidence: 71%
“…Neuropsin inhibitors (SPI3 and MUG I) are expressed by pyramidal neurons of the hippocampus (Kato et al 2001). Various forms of electrophysiological stimulation (kindling, LTP, stress) increase neuropsin expression within the hippocampus and in many other regions of the brain (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…These complexes have important clinical applications for differential diagnosis of prostatic diseases (21,22 ). Other kallikreins were also found to interact with specific proteinase inhibitors (23 ).…”
mentioning
confidence: 99%